2003
DOI: 10.1055/s-2003-38779
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Biliary Obstruction Caused by Portal Cavernoma

Abstract: While hemorrhagic complications of portal cavernoma are frequent, compression of the bile ducts by portal cavernoma is uncommon and treatment is still a matter for debate. We report here six new cases in order to describe: (a) the clinical, biological, and morphological features of this condition, and (b) the long-term results of a combined endoscopic and surgical treatment. The median age of patients at the time of diagnosis was 36.5 years. The circumstances of diagnosis were acute cholangitis (n=3), asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 23 publications
(45 reference statements)
3
58
0
8
Order By: Relevance
“…Cholangitis was reported in 5 of 10 patients managed with repeated stent exchanges in France, 12 in 4 of 6 patients managed by Dumortier et al 13 and in 3 of 13 patients (3 of 49 procedures; 6%) reported by Oo et al 10 In the series of 13 patients with symptomatic PCC reported by Khare et al, 11 none of the 10 patients who underwent endoscopic management developed cholangitis. However, recent experience from the same center noted that cholangitis was present at the time of 40 of 130 procedures (30%) in 20 patients managed with repeated stent exchanges over a period of 16 years and this was attributed to inability of patients to report for timely stent exchanges.…”
Section: Cholangitismentioning
confidence: 95%
See 4 more Smart Citations
“…Cholangitis was reported in 5 of 10 patients managed with repeated stent exchanges in France, 12 in 4 of 6 patients managed by Dumortier et al 13 and in 3 of 13 patients (3 of 49 procedures; 6%) reported by Oo et al 10 In the series of 13 patients with symptomatic PCC reported by Khare et al, 11 none of the 10 patients who underwent endoscopic management developed cholangitis. However, recent experience from the same center noted that cholangitis was present at the time of 40 of 130 procedures (30%) in 20 patients managed with repeated stent exchanges over a period of 16 years and this was attributed to inability of patients to report for timely stent exchanges.…”
Section: Cholangitismentioning
confidence: 95%
“…The first report of endoscopic extraction of common bile duct stones in PCC 8 was soon followed by other small series 5,[9][10][11][12][13] reporting success without an increase in complications, though some workers reported hemobilia during the procedure. [14][15][16][17] In many centers, endoscopic management has remained confined to establishing drainage of the obstructed biliary system before surgery, in the expectation that either the obstruction would resolve after a period of endoscopic drainage or that portosystemic shunt surgery (PSS), with or without second-stage biliary surgery, would provide definitive management.…”
Section: Evolution Of Endoscopic Therapy In Portal Cavernoma Cholangimentioning
confidence: 99%
See 3 more Smart Citations